Welcoming the Unwelcome: Refugee Flows, Refugee Rights, and Political Violence. - Savun, Burcu (International Studies Quarterly, 2022)
This article examines refugee-related violence by exploring the effect of extensive refugee rights on the risk of civil conflict and violent attacks against refugees by local population. The provision of fundamental rights, such as the freedom of movement, can reduce refugee groups' grievances, the risk of radicalization, and the ability of militant organizations to recruit refugees, thereby decreasing the risk of civil conflict. Regarding the behavior of local population toward refugees, two opposing effects of refugee rights may be at play. Extensive refugee policies may trigger civilian backlash by aggravating the perception of threat posed by refugees and increase the risk of civilian attacks against refugees. On the other hand, allowing refugees to integrate into society may provide economic benefits for locals and facilitate socialization between groups, reducing the motivation of citizens to target refugees. Using an original global dataset on refugee rights, I find that liberal refugee policies are associated with a reduction in the risk of civil conflict as well as anti-refugee violence in host states. This suggests that host governments and international organizations should give greater priority to guaranteeing refugee rights and promoting income-generating activities among uprooted populations to minimize potential security risks associated with refugees.